Stakeholders Engagement And Performance of Non-Governmental Organizations In Ethiopia - Zeleke, Lakachew; Guyo, Wario; Moronge, Makori (Innovation Journal of Social Sciences and Economic Review, 2023)
The objective of the study was to examine the influence of stakeholders’ engagement on the performance of NGOs in Ethiopia. The study utilized a mixed-methods approach (descriptive survey and correlational research designs) to collect quantitative data using a survey questionnaire. The study’s unit of analysis was the local NGOs, while the units of observation were the CEOs and board chairpersons of the sampled organizations. The systematic sampling technique and SPSS aided in data analysis. Suitable responses for analysis were received from 475 out of 654 questionnaires distributed. Among these, there were 276 responses from CEOs and 199 from board chairpersons. Stakeholders’ engagement influenced performance. However, there is a moderate level of stakeholder engagement among NGOs in Ethiopia. The study reveals that stakeholders’ engagement significantly positively influences the performance of local NGOs in Ethiopia. It has also been established that there is a moderate level of stakeholder engagement among NGOs in Ethiopia. These findings provide insights for enhancing stakeholders’ engagement among the local NGOs in Ethiopia and offer recommendations for future research. The findings were cross-sectional and can be generalized to local NGOs in Ethiopia. Therefore, future studies should consider a wider scope in terms of period and include other international NGOs in Ethiopia and those outside Ethiopia. Evaluation was also done based on internal stakeholders; hence, future studies should also consider views from external stakeholders.
Keywords: Stakeholders; Stakeholders Engagement; Performanc; Non-Governmental Organization